Effects of plyometric training on neuromuscular performance in youth basketball players: A pilot study on the influence of drill randomization - Hernández, S.; Ramirez-Campillo, R.; Álvarez, C.; Sanchez-Sanchez, J.; Moran, J.; Pereira, L. A.; Loturco, I. (Journal of Sports Science & Medicine, 2018)
The aim of this single-blind randomized controlled trial was to compare the effects of plyometric jump training (PJT), with (RG) and without (NRG) between-session drill randomization, on performance measures (i.e., jumping and sprinting abilities, change of direction speed, and technical performance) in youth male basketball players (age, 10.2 ± 1.7 years), assigned to either the NRG (n = 7), RG (n = 6), or control group (n = 6). Before and after the intervention, countermovement jump, 20-cm drop jump, 30-m sprint (with or without ball dribbling), and change-of-direction speed tests were completed. The PJT was applied twice per week for seven weeks. The only difference between PJT groups was the order of drill execution. An ANOVA was used to detect differences between study groups. The analyses revealed significant main effects of time (all p<.01; d = 0.64-0.89) and group x time interaction (all p<.05; d=0.31-51) for all examined variables. Post hoc analyses revealed moderate-large significant improvements for the RG (countermovement jump: 18.8%, d = 0.6; 20-cm drop jump: 23.9%, d = 0.80; 30-m sprint: 11.6%, d = 1.13; 30-m sprint with ball dribbling: 9.3%, d = 0.54; change of direction speed test: 14.6%, d = 1.82). In contrast, post hoc analyses revealed only small improvements for the NRG (20-cm drop jump: 14.1%, d = 0.36; 30-m sprint: 6.8%, d = 0.45; 30-m sprint with ball dribbling: 8.8%, d = 0.35; change of direction speed test: 10.5%, d = 0.49). Application of PJT without randomization is effective for improving physical and technical qualities. However, PJT could be more beneficial when executed with between-session randomization of drills.